WATCHING ATTITUDE FACTORS IN DELIVERING MUKBANG SHOWS - Styawan, Zenyt; Buwana, Danang Sangga (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Mukbang is an opportunity to find sustenance. This research using 8 concepts consisting of attraction in delivery, voyeurism mediation, perceptions of novelty, loneliness, health awareness, collectivity, social normatives and intentions watch. This study uses a positivism paradigm using quantitative approach and survey methods. The population in this study were adolescents age 15 to 17 years old. Based on research results this shows that the normative influence of Tanboy kun loneliness appeal to consciousness health with the collective perception of novelty in mediating voyeurism the delivery of mukbang (X) affects the intention to watch (Y) students of SMKN 1 Bekasi.